Антиномія письма – голосу в "трьох хвилинах" Лесі Українки - Гайдамачук, Ольга Володимирівна (Enigma corporation, 2022)
The article is devoted to the analysis and interpretation of the hidden and still unexplored antinomy of the writing and the voice in Lesya Ukrainka’s philosophical dialogue "Three Moments". This antinomy is conducted through all three moments, and, therefore, is not accidental. Each of the three moments continues in its acoustic space with the corresponding audio accompaniment, which determines the goal – to analyze the intonation structure of the poem. Club, prison, emigration – the space of moments of a different "intonation crisis" of Girondist, who wants, but can not write for different reasons. The letter itself ultimately brings him doom (from the letters of the one who decided to write). It has been found that the deep basis of the three moments is the archetype of the triple soul, each one responds to its challenge in a certain time and space. From the "cultural" space of the club, where the conf lict of the Mind with the Heart arises, the moments of Girondist’s life pass through the prison space to the "natural" space in exile. His intonation crises are as follows: 1) one who intones vividly but does not write; 2) one who wants to, but cannot write due to internal detonation; 3) one who is desperate and exhausted in the articulation of writing. Every crisis is provoked and asked by Montagnard. The transformations of the Girondist worldview caused by him seem irreversible. Great power is attributed to writing: from the power to grant privileges, to broadcast testaments, to unite the hearts of friends – to powerful ambitions, powerful destructive intentions, equivalent to the strength of a strong army or the aim of a sniper bullet. The voice yields to the power of writing and is defeated in a battle with the archives of memory. But the power of writing is undermined by despair and emotional exhaustion.
Antinomy of writing – voice in "three moments" by Lesya Ukrainka
Keywords: інтонація; артикуляція; детонація; книга; текст; діалог; статути